Profits First, Safety Second: Canada’s Occupational Health and Safety System at 50 - Foster, Jason; Cake, Susan; Barnetson, Bob (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
This article argues that while workplaces are safer today than they were 50 years ago, the degree to which this change is due to Canada’s occupational health and safety (ohs) system is unclear. Examining the literature and reflecting upon the authors’ own experiences with workplace safety, the article suggests that fundamental flaws embedded in the principles of the system undermine its effectiveness at keeping workers safe. Specifically, the premise of joint responsibility – which is given life in the internal responsibility system (irs) – appears to ignore the conflicting interests and unequal power relations that exist in Canadian workplaces. The circumstances that contributed to the historical effectiveness of the irs no longer exist, undermining the ability of workers to realize safe and healthy workplaces.